Non‐steroidal anti‐inflammatory drugs (NSAIDs) for cancer‐related pain in children and adolescents - Cooper, Tess E (Cochrane Database Syst Rev, 2017)
This is a protocol for a Cochrane Review (Intervention). The objectives are as follows: To assess the analgesic efficacy, and adverse events, of non‐steroidal anti‐inflammatory drugs (NSAIDs) used to treat cancer pain in children and adolescents between birth and 17 years, in any setting.